Topical application of eosin 2% with cloroxilenol 0.3%, propylene glycol 30% (neomercurocromo) and colloidal silver: a new topical treatment for lichen sclerosus - CARLO MARETTI; GIORGIO CAVALLINI (International Journal of Pharma and Bio Sciences, 2018)
Our aim is to evaluate safety and efficacy of topical Eosin 2% + Chloroxylenol 0.3% + Propylene glycol 30% (Neo mercurocromo) and Colloidal Silver to improve Lichen Sclerosus (LS) symptoms.We postulated that the disinfectant, anti-moist, anti-dystrophic, antifibrotic and cytoprotective activity of NEOMercurocromomight be of help in improving LS symptoms. Forty-four LS patients were randomised into two groups: 22 patients received the active drugs (Group 1) and 22 received the placebo (NaCl 0.9%) for 4 weeks (Group 2). The active drugs were used for two weeks each: NEOMercurocromo first and subsequently Colloidal Silver. Active drugs and placebo were rubbed with a sterile gauze on the LS lesions twice a day. Three clinical controls using a photo archive (baseline, and one and three months after active drug or placebo delivery) were carried out on each patient using a specific LS scale score, and the Dermatology Life Quality Index (DLQI) score. One and three months after active drugs or placebo delivery, the patients defined their post-treatment condition using the Patient Global Impression of Improvement (PGI-I) scale. The scores were compared within and between groups using non parametric tests, and the side effects were compared between the groups using the Chi-squared test (χ²). The LS and the DLQI scores were similar between the groups at baseline. Both scores significantly improved in Group 1 to a larger extent than in Group 2 at one and three months. The PGI-I score in Group 1 was higher than in Group 2 at one and three months. No side effects emerged in either group. NEOMercurocromo + Colloidal Silver is a safe and efficient therapy for LS.